The real thing - Di Bart, Tony; Drayton; Cleveland City Blues; Form Private Limited (United Kingdom : Cleveland City Blues, 1993)
Contains five different mixes of the single.
CD 1 : New 7' Dance -- New 7' Radio -- New 12' Dance -- Original 12' Dance -- 12' Dub Mix.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Dance music